Role of Pap’s smear and visual inspection of cervix with Lugol’s iodine for early detection of premalignant and malignant lesions of cervix: a cross sectional study - Vyas, Kirtan M.; Bhalodia, Kalpesh S.; Thakor, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Carcinoma of cervix is the third most frequently diagnosed cancer in Indian women. Carcinoma of cervix, due to its slow progression from pre-cancerous lesion to malignancy and easy accessibility to examination, gives us ample opportunity for early detection and thus considerably improved prognosis. To screen patients coming to GOPD at the age of 18-60 years by Pap smear and VILI and to detect specificity and sensitivity of each test for detecting CIN ( Cervical Intraepithelial Neoplasia) and Ca Cervix. Methods: The present study was conducted in the Department of Obstetrics and Gynaecology, Smt. NHL Municipal Medical College and Hospital, Ahmedabad during October 2008 to October 2010. Total 50 women (18- 60 yrs) who fulfill selection criteria underwent pap smear and VILI. In pap smear and/or VILI positive patients, cervical biopsy and histopathological examination were done. The sensitivity and specificity of each test were determined and compared. Results: Out of total 50 women, 20 (40%) women were in the age group of 30-39 years. 64% women had coitage before 20 years. 56% of the women had 3 or more children. 74% of the patients came with chief complaint of vaginal discharge followed by lower abdominal pain in 10% of the patients. On visual inspection with lugol’s iodine (VILI), squamo-columnar junction was seen in 66% of the women. Out of 50 women, 5 (10%) women tested positive for cytology results. Out of 50 Women, 8 (16%) women came out to be VILI test positive. The sensitivity, specificity, positive predictive value and negative predictive value for VILI test are 80%, 91.11%, 50%, 97.6% respectively. The sensitivity, specificity, positive predictive value and negative predictive value for Pap test are 80%, 97%, 80%, 97% respectively. Conclusions: VILI has almost equal sensitivity as compared to Pap (Cytology) test but Pap (Cytology) test has higher specificity compared to VILI.